Structures and properties of alkanethiol-modified graphene oxide/solution-polymerized styrene butadiene rubber composites: Click chemistry and molecular dynamics simulation. (16th June 2018) - Luo, Yanlong; Wu, Youping; Luo, Kaiqiang; Cai, Fei; Zhai, Tianshu; Wu, Sizhu
Abstract: Alkanethiol-modified graphene oxides (GOs) containing alkanethiol (C x GO) molecules with varying chain lengths were synthesized through click chemistry. Then, C x GO/solution-polymerized styrene butadiene rubber (C x GO/SSBR) composites with different C x GO loadings were prepared by a solution-mixing method. By combining experiment and molecular dynamics (MD) simulation, we investigated the relationship between the microstructures and properties of the C x GO/SSBR composites. Results showed that the 1-heptanethiol-modified GO (C7 GO)/SSBR composite had the smallest fractional free volume and the least mobility of the polymer chains. Moreover, the 1-octadecanethiol-modified GO (C18 GO)/SSBR composite displayed the largest binding energy (E binding ). Thermal stability, gas barrier, dynamic, and static mechanical properties were improved by introducing C x GO. The long chain length of C x GO indicated that the composites had good performance. We believe that these results provide a basis for the design and fabrication of high-performance GO/SSBR composites.